Environmental factors and suicide in Australian farmers: A qualitative study. Issue 5 (3rd September 2019) - Perceval, Meg; Kõlves, Kairi; Ross, Victoria; Reddy, Prasuna; De Leo, Diego
ABSTRACT: Farmers and farm workers have been recognized as a group at high risk of suicide in Australia. This study aims to identify and better understand environmental factors associated with suicide among Australian farmers and farm workers. Qualitative analysis was undertaken in accordance with the Consolidated Criteria for Reporting Qualitative Research. Male and female focus groups were conducted separately with people who lived or worked on a farm in six farming communities. Qualitative analyses showed that a number of environmental influences may contribute to the increased risk of suicide: extreme climatic events; isolation; service availability; access to, and frequent use of firearms; death and suffering of animals; government and legislation; technology; and property values. Both the physical and socio-cultural environments in which farmers operate appear to contribute to farmer suicide and need to be considered in suicide prevention.